Strategies and Approaches for Antibiotic Yield Improvement in Actinomycetes - Shi, Zhenping; Zhang, Jiuming; Tian, Li (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Actinomycetes represent a valuable source of commercially significant antibiotics. However, the yields of antibiotics in wild Actinomycetes usually could not meet the commercial needs and so antibiotics yield improvement is a constant requirement in the drug industry. Various methods and strategies such as traditional strain breeding methods and fermentation optimization methods have been tried and some new ideas such as gene engineering, mixed culture and quorum sensing along with empirical approaches are still on the way to gain this ultimate goal. This review will focus on the strategies and approaches for Actinomycetes antibiotics augment.